2014
DOI: 10.1038/jp.2014.90
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal predictors and body composition of large-for-gestational-age newborns: perinatal health outcomes

Abstract: OBJECTIVE:To compare body composition of large-for-gestational-age (LGA) with appropriate-for-gestational-age (AGA) newborns and to identify antenatal predictors of LGA. STUDY DESIGN: This cross-sectional study included 536 term, singleton infants. Anthropometric measurements were performed within 48 h of birth and included determination of body fat percentage (%BF) by air displacement plethysmography. Associations were investigated using logistic regression. RESULT:LGA infants had greater %BF (P o 0.001) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Objects such as name bracelets and cord clamps affect body mass and volume readings and consequently FM and FFM. Some but not all studies reported adjusting for these objects [ 53 , 58 , 72 , 76 , 80 , 89 , 90 , 98 , 108 ]. Ramel et al [ 108 ] also adjusted for other objects such as nasogastric tube and oximetry monitor.…”
Section: Resultsmentioning
confidence: 99%
“…Objects such as name bracelets and cord clamps affect body mass and volume readings and consequently FM and FFM. Some but not all studies reported adjusting for these objects [ 53 , 58 , 72 , 76 , 80 , 89 , 90 , 98 , 108 ]. Ramel et al [ 108 ] also adjusted for other objects such as nasogastric tube and oximetry monitor.…”
Section: Resultsmentioning
confidence: 99%
“…Unmodifiable risk factors include maternal age, parity, parental height, ethnicity, fetal sex (male), and previous macrosomic delivery ( 224 , 236 238 ).…”
Section: Discussionmentioning
confidence: 99%
“…LGA is associated with higher body weight and body fat (%) and slower postnatal weight gain compared to what is considered appropriate for gestational age (AGA) and being SGA is associated with lower body weight and body fat (%) at birth and higher postnatal weight gain compared to AGA (11,12,13).…”
Section: At Birth Beingmentioning
confidence: 99%
“…Body composition was assessed using Pea Pod Infant Body Composition System (LMI Concord, CA, USA) software 3.0.1. Its physical design and measurement procedures have been described elsewhere in detail (13). The Pea Pod has been validated and found to have high reliability and compliance to reference methods (15,16).…”
Section: Body Compositionmentioning
confidence: 99%